Integrasi Nilai Aik Dalam Pengembangan Karakter Bersih Melalui Program Sisarah di Sekolah Dasar - Alistina; Nurmarina Malik Fadjar (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
This study aims to explore the integration of religious, scientific, and moral values (AIK) in the development of cleanliness character among elementary school students through the SISARAH program. Using a qualitative approach, the research involves observations, interviews, and analysis of relevant documents. The findings indicate that AIK values can strengthen students’ cleanliness character, as reflected in their daily behavior. The implementation of the SISARAH program contributes not only to increasing environmental awareness but also to the moral and ethical development of the students.